PENGEMBANGAN MEDIA PPT INTERAKTIF: ACTIVE-SLIDE PADA MATERI “MELIHAT KARENA CAHAYA” UNTUK SISWA KELAS V SD - Btari Maharani; Edelweiss Milkana Diva; Zahwa Aulia; Anastasya Dewi Ambarwati; Ningrum Melihayatri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop Canva-based interactive multimedia learning content called Active-Slide for the topic "Seeing Because of Light" for fifth-grade elementary school students and evaluate its feasibility based on expert assessments. The research method employed was Research and Development (R&D) following the 4D (Four-D) development model, which was adapted up to the development stage focusing on product validity testing. Feasibility data were collected using a 1–5 Likert scale questionnaire involving media experts, language experts, and material experts. The validation results were then analyzed using quantitative descriptive techniques. The results indicated that the feasibility of the Active-Slide interactive multimedia achieved a score percentage of 85.7% from media experts (highly feasible), 92.5% from language experts (highly feasible), and 87.5% from material experts (highly feasible). Consequently, the developed Active-Slide media is declared highly feasible for use as an interactive, engaging, and student-centered science learning tool to support concept understanding and science process skills in elementary schools.